Self-healing in fiber-reinforced alkali-activated slag composites incorporating different additives. (30th November 2020) - Zhang, L.V.; Suleiman, A.R.; Nehdi, M.L.
Highlights: Potential self-healing of alkali-activated slag-based composites was explored. X-ray -μCT with 3-dimensional image segmentation showed evidence of self-healing. AAM specimens incorporating crystalline additives exhibited significant self-healing. Healing occurred at surface cracks and calcium carbonate was prevalent self-healing product. Higher pH and calcium ions and using PVA acted synergistically to accelerate crack self-healing. Abstract: Despite that considerable research has explored self-healing of portland cement-based materials, potential self-healing in alkali-activated binders remains largely unexplored. Therefore, this paper deploys a wide array of experimental techniques to investigate the self-healing properties of PVA fibre-reinforced alkali-activated slag-based composites incorporating crystalline additives (CA) and bentonite minerals (BN). X-ray microcomputed tomography (μCT) with three-dimensional image segmentation and analysis, scanning electron microscopy with energy dispersive X-ray (SEM-EDS) analysis, inductively coupled plasma optical emission spectroscopy (ICP-OES), optical microscopy, and water sorptivity measurements were used to visualize, quantify, and identify the nature of healing compounds. While specimens incorporating CA exhibited significant self-healing, less self-healing was observed in specimens incorporating bentonite. X-ray μCT results indicated that the healing mechanism mainly occurred at surface cracks and calcium carbonate was the prevalent self-healing product formed. It was found that rising the pH and concentration of calcium ions of the curing medium and using polyvinyl alcohol (PVA) fibers in the mixture acted synergistically to accelerate crack self-healing in alkali-activated slag composites.